Propuesta de un sistema para el tratamiento de aguas residuales de la empresa Food & Drinks Alimentos SAS a nivel laboratorio (2020)
The Colombian company Food & Drinks Alimentos SAS is located in Cota, Cundinamarca, processing a dairy products. It has a weekly reception of 1000 L of milk, however, it hasn`t a system for water treatment. The water requires a physical, chemical and economic study to establish each of the equipment to be used and to reduce the environmental impact generated as now. Through the balance, the company discharges of 2.5 m3 / daily of residual industrial water. The characterization by the QUIMICONTROL laboratory allowed to know the limits of parameters, these are some parameters above the limit: pH, BOD5, COD, fats and oils.